Roadmap for strategic and tactical planning: implementation of an Integrated Agri-food System Initiative (IASI) - International Maize and Wheat Improvement Center; Alliance of Bioversity International and CIAT (International Maize and Wheat Improvement Center, 2022)
The complexity of agri-food systems demands increasing cross-institutional coordination and collaboration to strengthen science-based decision-making and agricultural planning. Reaching impact at scale requires not only scientific and technical innovations, but a better integration of political, social, economic, health, and environmental considerations through institutional innovations. The Integrated Agri-food System Initiative (IASI) is a multi-sector methodology that aims to (i) understand the challenges of a target agri-food system at a regional, national or local level, and (ii) identify a widely agreed solution set and realistic targets for a future improved agri-food system (Govaerts et al., 2021). Building on diverse existing knowledge resources, IASI facilitates a mindset shift towards sustainable and scalable innovations and stakeholder consensus on multi-partner and multi-scale integrated programs. The purpose of this roadmap is to guide development and implementation of the IASI methodology in any location by sharing best practices, enabling factors and useful tools, based on previous IASI cases. The IASI methodology has been developed to be an inclusive and participatory process that builds consensus through design thinking (i.e. understanding specific needs to define an innovative solution), informed by situation analysis, modeled predictions, and scenarios for a discontinuous future. This document’s primary intended users include stakeholders interested in large-scale planning to improve agri-food systems in distinct socioecological settings. Commonly, these stakeholders will be governments (Ministry of Agriculture, Ministry of Territorial Planning), CGIAR centers or National Agricultural Research and Extension Systems (NARES) that can serve as knowledge brokers. Application of the IASI methodology can generate strategies and quantitative SDG-aligned targets that have greater likelihood of supportive public and private investment. It emphasizes timely provision of information, options, and strategies to decision makers and multiple entry points for stakeholders with different interests (e.g. policymakers, rural communities, market players, banks, individuals). Moreover, the strategies and actions emerging from the IASI methodology reduce economic, reputational, operational and policy risks faced by governments, global donors, and agricultural sector financiers by offering a validated set of potential investments.